A Study on Students’ Reading Ability at Second Year Students of STKIP PGRI Sumatera Barat - Sesmiyanti Sesmiyanti (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2017)
This research is aimed to find out the students’ reading ability in comprehending the text at the second years of STKIP PGRI Sumatera Barat. The population of the research was 76 students. The researcher used total sampling population and took all population as the sample. In collecting data, the researcher used classroom test. Test is used to find out the students’ reading ability. Students’ reading ability is categorized into very good, good, enough, less, and failed. Based on the result of the research, It can be seen that mean score of students’ reading abilityscore is 63.2. It is enough level, so it can be concluded that the students’ reading ability is enough or sufficient